A practical procedure for the multigram synthesis of the SuperQuat chiral auxiliaries - Bull, S; Davies, S; Jones, S; Polywka, M; Prasad, R; Sanganee, H (1998)
An efficient and simple synthesis of oxazolidin-2-one SuperQuat chiral auxiliaries is described which provides rapid access to multigram quantities of the auxiliaries.